"NEWBORN MACROSOMIA: INCIDENCE AND MORBIMORTALITY" - Alzamora Valencia, Ada (2015)
618 macrosomic babies in a population of 8,880 live births (6.9%) was studied. For purposes of our analysis considered 500 cases, finding the association of certain maternal and fetal macrosomia factors such as parity and age (43%), gestational age of 39 weeks or more (90%), maternal diabetes (1.9%) male (65%). The application of vacuum extractor was double that of the general population (4 .6%: 2.1%). Macrosomia morbidity was twice the normal newborn weight (28%: 14%). The incidence of asphyxia, meconium aspiration and trauma at birth increased the weight. The neonatal mortality rate in macrosomic was 8%, the cause of death related in particular to fetal size. To improve the prognosis of infant macrosomia, you must establish a pediatric-obstetric combined management aimed at identifying the population at risk and prenatal detection of macrosomia in an attempt to reduce morbidity associated with event delivery.